Cortisol diurnal changes during pregnancy and subclinical anxious-depressive maternal symptomatology: A follow-up study of the EPI_Maternal_Project cohort. (September 2021) - Castro-Quintas, Águeda; Daura-Corral, Maria; Eixarch, Elisenda; Fuente-Tomás, Lorena de la; Martin-González, Nerea San; Rocavert-Barranco, Mireia; Miguel-Valero, Alba; Crispi, Fatima; Marques-Feixa, Laia; Palma-Gudiel, Helena; García-Portilla, Mari Paz; Fañanás, Lourdes
Abstract : Introduction: Pregnancy is considered an important process, since different stressors during gestation could affect maternal mental health and fetal neurodevelopment. Stress is regulated by the steroid hormone cortisol. Although cortisol production increases along pregnancy, an excess has been associated with fetal neurotoxic complications. Goals: To study cortisol circadian rhythm changes throughout pregnancy and its association with sub-clinical maternal psychopathology. Materials And Methods: 112 healthy primiparous pregnant women collected four saliva samples throughout one day at 12th, 22th and 32th weeks of gestation to analyze cortisol. Stress perception and depressive symptomatology were evaluated following PSS and EPDS criteria, respectively. Results: As expected, pregnant women showed increasing cortisol concentrations (AUCg) throughout the pregnancy (F=6.830, p=.002). However, women with risk for depression showed higher cortisol concentrations during pregnancy (F=7.566, p=.007) with a less pronounced decrease at the end of day at 12th and 22th weeks. Conclusion: Our study suggest that subclinical depressive symptoms at first half of pregnancy compromises maternal and fetal wellbeing due to excessive cortisol levels.